Linguistic Features in the Game Chat of Rise of Kingdom - Kusumawardhani, Paramita; Setiawan, Louis Marco (ITScience (Information Technology and Science), 2025)
The rapid development of online games has given rise to dynamic virtual communities, where language plays a central role in strategic coordination and social bonding. The participants were the players of Rise of Kingdoms Game and the data were taken from the chat between the players. This study examined the linguistic characteristics used in Rise of Kingdoms (RoK) chat and how these elements have function in communication between players. Qualitative descriptive discourse analysis was used to collect data in the form of randomly selected English conversation logs through manual transcription of alliance messages and private conversations. The study identified five main categories of abbreviations as the result, such as TP for teleport, technical acronyms like AoE and YSG, register loans like DM, metaphorical extensions like Kraken for high-spending players, and player identity markers like F2P.